Cast immobilisation in situ versus open reduction and internal fixation of displaced medial epicondyle fractures in children between 7 and 16 years old. A study protocol for a randomised controlled trial - Hämäläinen, Tero (BMJ Open, 2021)
INTRODUCTION: Medial epicondyle fracture of the humerus is a common injury in childhood. There is uniform agreement that minimally displaced fractures (dislocation ≤2 mm) can be treated nonoperatively with immobilisation. Open fractures, fractures with joint incarceration or ulnar nerve dysfunction require surgery. There is no common consensus in treatment of closed medial epicondyle fractures with >2 mm dislocation without joint incarceration or ulnar nerve dysfunction. We hypothesise that there is no difference in treatment outcomes between nonoperative and operative treatment. METHODS AND ANALYSIS: This is a multicentre, controlled, prospective, randomised noninferiority study comparing operative treatment to non-operative treatment of >2 mm dislocated paediatric medial epicondyle fractures without joint incarceration or ulnar nerve dysfunction. A total of 120 patients will be randomised in 1:1 ratio to either operative or nonoperative treatment. The study will have a parallel nonrandomised patient preference arm. Operative treatment will be open reduction and internal fixation. Nonoperative treatment will be upper limb immobilisation in long arm cast for 4 weeks. Data will be collected at baseline and at each follow-up up to 2 years. Quick-DASH is used as primary outcome measure. Secondary outcomes are patient-reported pain, differences in range of motion, Pediatric Quality of Life Inventory, cosmetic visual analogue scale and Mayo Elbow Performance Score. ETHICS AND DISSEMINATION: Ethical approval has been obtained from Helsinki University Hospital (HUS) ethical board HUS/1443/2019. Each study centre has obtained their own permission for the study. A written authorisation from legal guardian will be acquired and the child will be informed about the trial. Results of the trial will be disseminated as published articles in peer-reviewed journals. TRIAL REGISTRATION: The trial has been registered at clinicaltrials.gov with registration number NCT04531085.